Electron Microscope Study of Human NB and SMH Cells Infected with the Parvovirus, H-1: Involvement of the Nucleolus* - Al-Lami, F.; Ledinko, Nada; Toolan, Helene (Journal of General Virology, 1969)
SUMMARY The sequence of changes in human NB and SMH cells that occurred after H-1 virus infection, was studied with the electron microscope. The earliest alterations in NB cells after infection were detected in the nucleolus, after 31 hr. The pars fibrosa appeared devoid of its formed elements and was occupied instead with mainly ‘incomplete’ H-1 virus. The pars granulosa was more diffuse than normal and its nucleolar granules more sharply defined. A few ‘incomplete’ and ‘complete’ virus particles were scattered about the nucleus at approximately the same time. The cytoplasm was intact. Shortly thereafter, margination of the nuclear chromatin occurred. The nucleoli became increasingly condensed and shrunken, and apparently formed a doughnut-shaped body with condensed walls containing empty virus. Eventually, most of the nucleolar elements disappeared as the nuclei filled with complete and incomplete virus particles as well as occasional crystals possibly of protein nature. As the nucleolus disappeared, the cytoplasm disintegrated except for a few scattered mitochondria and some recognizable areas of endoplasmic reticulum which contained complete virus particles in linear array. Seventy-seven hr after infection when the nucleus had also broken down, virus was found associated with the disintegrated nucleus, within fragments of endoplasmic reticulum, and attached to thickened and adjoining plasma membranes of the few remaining, apparently uninfected cells. In SMH cells basically similar changes occurred except that the nucleoli appeared to fragment 31 hr after infection. Later, though most of the nucleolar sections disappeared, a few persisted and formed ‘nucleolar inclusions’ identical to those observed in NB cells. In contrast to the mixture of ‘complete’ and ‘incomplete’ virus observed in NB cells, the virus found in SMH cells was almost exclusively ‘empty’. Virus seen outside the nucleus, either in NB or SMH cells, appeared complete.